2023
DOI: 10.1007/s10729-022-09626-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting no-show appointments in a pediatric hospital in Chile using machine learning

Abstract: The Chilean public health system serves 74% of the country’s population, and 19% of medical appointments are missed on average because of no-shows. The national goal is 15%, which coincides with the average no-show rate reported in the private healthcare system. Our case study, Doctor Luis Calvo Mackenna Hospital, is a public high-complexity pediatric hospital and teaching center in Santiago, Chile. Historically, it has had high no-show rates, up to 29% in certain medical specialties. Using machine learning al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Dashtban et al [24] considered eight variable groups for prediction of non-attendance, including demographic data, patient history, appointment characteristics, time variables, patient appointment history, socioeconomic data of the patient, weather conditions and admission history. A study by Dunstan et al [25] from Chile concluded that factors pertaining to a socioeconomically disadvantaged background were the most relevant to predict noshows. The predictive value of variables linked to low socioeconomic status have also been observed in other studies, although there seems to be a country-speci c component [6, 26], which further strengthen the need for models highly adjusted to the local patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Dashtban et al [24] considered eight variable groups for prediction of non-attendance, including demographic data, patient history, appointment characteristics, time variables, patient appointment history, socioeconomic data of the patient, weather conditions and admission history. A study by Dunstan et al [25] from Chile concluded that factors pertaining to a socioeconomically disadvantaged background were the most relevant to predict noshows. The predictive value of variables linked to low socioeconomic status have also been observed in other studies, although there seems to be a country-speci c component [6, 26], which further strengthen the need for models highly adjusted to the local patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as reminders, available appointment times, wait times, patient education, and procedure quality affect patients' likelihood of attending their appointments [8,9]. At the same time, economic conditions, health insurance, and transportation also cause patients to miss their appointments [10,11]. Health systems develop effective strategies by taking these factors into account to increase patients' "show-up" situations and reduce "no-show" situations [8].…”
Section: Introductionmentioning
confidence: 99%